Transcriptomic analysis identified SLC40A1 as a key iron metabolism-related gene in airway macrophages in childhood allergic asthma - Wang, Zhili; He, Yu; Cun, Yupeng; Li, Qinyuan; Zhao, Yan; Luo, Zhengxiu (Frontiers in Cell and Developmental Biology, 2023)
Asthma is the most common chronic condition in children, with allergic asthma being the most common phenotype, accounting for approximately 80% of cases. Growing evidence suggests that disruption of iron homeostasis and iron regulatory molecules may be associated with childhood allergic asthma. However, the underlying molecular mechanism remains unclear. Here, three bulk transcriptomic datasets were used to detect aberrant expression profiles of iron metabolism-related genes in childhood allergic asthma. Five common iron metabolism-related differentially expressed genes (DEGs) were identified, which were functionally related to iron homeostasis. Among these genes, SLC40A1 was strongly correlated with type 2 airway inflammatory markers and the gene signature of SLC40A1 could potentially be used to determine type 2-high and type 2-low subsets in childhood allergic asthmatics. Further single-cell transcriptomic analysis identified airway macrophages driving SLC40A1 expression. Results further indicated reduced iron levels in the bronchoalveolar lavage (BAL) fluid, but increased iron accumulation in BAL cells in childhood allergic asthma patients. Furthermore, decreased expression of SLC40A1 was confirmed in airway macrophages of childhood allergic asthmatics with SLC40A1 expression correlating with reduced iron levels in the airways. Overall, these findings reveal the potential role of the iron metabolism-related gene SLC40A1 in the pathogenesis of childhood allergic asthma.